Analysis of stress gradients in physical vapour deposition multilayers by X‐ray diffraction at fixed depth intervals. (4th February 2014) - Fischer, G.; Selvadurai, U.; Nellesen, J.; Sprute, T.; Tillmann, W.
<x xml:space="preserve">Abstract</x> The objective of this article is to develop and apply a model for the design and evaluation of X‐ray diffraction experiments to measure phase‐specific residual stress profiles in multilayer systems. Using synchrotron radiation and angle‐dispersive diffraction, the stress measurements are performed on the basis of the sin2ψ method. Instead of the traditional Ω or χ mode, the experiments are carried out by a simultaneous variation of the goniometer angles χ, Ω and ϕG to ensure that the penetration and information depth and the measuring direction ϕ remain unchanged when the polar angle ψ is varied. The applicability of this measuring and evaluation strategy is demonstrated by the example of a multilayer system consisting of Ti and TiAlN layers, alternately deposited on a steel substrate by means of physical vapour deposition.